Strategi Menjaga Keamanan Data dalam Sistem Perpustakaan Digital - Billy Arya Nugraha; Anwar, Rully Khairul; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Pustabiblia: Journal of Library and Information Science, 2025)
This research discusses identifying data security threats in digital library systems, developing prevention strategies, and evaluating the impact of breaches on user trust. Research focus includes improving network security, data encryption, protection from malware attacks, and staff training regarding information security. This research aims to improve the security and reliability of digital library systems, as well as increase user awareness of the importance of data security. This research uses a literature review method of references related to the topic of digital libraries and data security with a total of seven references in journal form. This research discusses the challenges, strategies, and influence of strategies in maintaining data security in digital libraries. Challenges include accessibility, collection protection, digital skills, and privacy protection. The proposed strategy includes access protection, data encryption, threat monitoring, security awareness training, and incident preparedness. Implementation of this strategy is expected to improve data security, increase user trust, and maintain the relevance of digital libraries in the current digital era. Developing a mature strategy is the main factor in overcoming data security challenges in digital library systems. Threat analysis shows that unauthorized access, malware attacks, identity theft, and sensitive data leaks are the main challenges. To address this, increased access protection, data encryption, threat monitoring and security awareness training are required. Incident prevention strategies, such as firewalls and intrusion detection systems, can reduce the risk of attacks. Data security breaches can reduce user trust, but effective recovery efforts can repair the damage and rebuild user trust.